2020
DOI: 10.20896/saci.v8i1.615
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with ‘Caste’: Curriculum, Pedagogy and Reception

Abstract: Caste has been a persisting form of stratification that continues to evade equality and social justice in Indian society. Among the routes to tackle the menace of caste has been the education system. In this regard, the National Curriculum Framework 2005 came with a resolute to engage the students with different issues, including that of caste with a critical and empathic eye. This paper locates the challenges to this curriculum by focusing on the pedagogy and reception of the curriculum. In doing so, it argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Kirasur (2021), however, is critical of the attempt and cites instances from the history and political science NCERT textbooks to claim that they ‘implicitly and explicitly’ uphold caste hierarchy. Mittal (2020) in her 2015–2016 study analysed the NCERT social science textbooks for Classes 6–10 for their content on caste-based inequalities and examined how students in a government-aided school in Delhi engaged with it. The findings of a questionnaire administered to 86 students from Class 9 to understand their opinion about caste-based discrimination revealed that 44.19% of the students denied its prevalence, and barely a quarter of the sample accepted that caste-discrimination still exists.…”
Section: The Schooling Of Castementioning
confidence: 99%
“…Kirasur (2021), however, is critical of the attempt and cites instances from the history and political science NCERT textbooks to claim that they ‘implicitly and explicitly’ uphold caste hierarchy. Mittal (2020) in her 2015–2016 study analysed the NCERT social science textbooks for Classes 6–10 for their content on caste-based inequalities and examined how students in a government-aided school in Delhi engaged with it. The findings of a questionnaire administered to 86 students from Class 9 to understand their opinion about caste-based discrimination revealed that 44.19% of the students denied its prevalence, and barely a quarter of the sample accepted that caste-discrimination still exists.…”
Section: The Schooling Of Castementioning
confidence: 99%
“…Teaching caste in classrooms is a difficult task, both pedagogically and ideologically and teachers need to engage with the curriculum to present a critical perspective (George & Madan, 2009). Students often render caste as "exotic" and "distant" (Shankar, 2017;Mittal 2020). Hence, discussing caste in classrooms requires historicizing it and making students aware of their preconceptions.…”
Section: Pedagogical Interventions: Amnesia To Uncasting the Curriculummentioning
confidence: 99%
“…The classrooms, in the experience of Dalits, instead, work as sites where one confronts the brutal reality of caste." Social stratifications mark their presence quite overtly in classrooms and "who does/does not see caste in classroom, is associated with caste privilege" (Pan, 2022;Mittal, 2020). Hence, while on one hand, upper caste students claim "caste as a practice of the past and denies witnessing it in contemporary society" (2020, p. 106) often denying its existence (Pan, 2022), on the other hand, students from the marginalised communities maintain silence (Mittal, 2020) or look for alternative articulations of their identities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations